As práticas integrativas complementares em saúde como dispositivo de promoção da saúde no trabalho: uma proposta de intervenção na Universidade Federal Fronteira Sul - Rodrigeri, Marisete (2022)
Complementary Integrative Practices (CIPs) are preventive therapeutic resources and health promotion that aim to stimulate the body's natural mechanisms (DACAL, SILVA, 2018). This study aims to propose an Action Plan based on CIPs at Universidade Federal Fronteira Sul (UFFS), with a view to generating health promotion for servers. It also seeks to contribute to the prevention of absenteeism and the prevention of diseases related to the exercise of laboral activities. It is a research that used the explanatory sequential mixed method, this approach uses an expanded methodology that interconnects the quantitative and qualitative approaches. The first stage of the research was quantitative, through an online questionnaire to servers with active institutional e-mail, which was answered by 309 servers. The second stage was qualitative, through a Focus Group (FG) formed from the servers who participated in the first stage and who chose to participate in the FG and the information was collected through semi-structured questions. For the analysis of the FG data, thematic content analysis proposed by Minayo (2010) was used. The analysis of quantitative data was performed using simple statistics and later joined to qualitative data, which formed the set that revealed three categories of thematic analysis which were named: a) Knowledge, interest and access of servers to CIPs; b) Promotion of health the individual as an active agent of his/her health; and c) Continuous availability of CIPs in the work environment. The set of quantitative and qualitative analyzes revealed that among the most known CIPs among the servers of the total of 309 respondents, 72.5% reported that they know some CIPs, with Reiki being the most cited, with 24.0%. These categories also showed that, in general, the servers know several of the CIPs contained in the National Policy for Complementary Integrative Practices (NPCIP). They also reveal the interest of the servers in relation to the theme of CIPs, with 96% of the servers expressing themselves in favor of the implementation of CIPs in the work environment at UFFS. Also, they indicated that the servers consider the CIPs as a health promotion instrument, which is the main reason for their use. It showed that servers would incorporate CIPs into their routine if they had easier access. Based on the results of this study, a final product was proposed and prepared, which will be delivered to the Directorate of Attention to Server Health (DASS), containing an Action Plan on CIPs to offer CIPs to servers and also suggestions for possible expansions of this plan, which have the potential for future realization at UFFS, in order to provide information and assist in the formulation of actions aimed at promoting health, improving the quality of life, well-being and satisfaction of UFFS servers. These results allow us to conclude that the servers are interested in the CIPs being implemented at UFFS. Thus, the interest of management in the inclusion of these practices with the objective of promoting the health of the servers and preventing absenteeism becomes fundamental.